KONSELING HUMANISTIK SEBAGAI UPAYA PEMBERDAYAAN KERJA TUNAWISMA USIA DEWASA: STUDI KASUS DI RUMAH SINGGAH DINAS SOSIAL SURAKARTA - Lucretia Anggie Rahma Surya (STKIP Subang, 2026)
This study aims to describe the condition of adult homeless individuals aged 30–40 years, analyze the application of humanistic counseling, and explain its impact on self-awareness as a foundation for work empowerment at the Surakarta City Social Service Shelter House. This study uses a qualitative method with a descriptive approach. The research subjects consisted of five homeless individuals aged 30–40 years, with supporting informants including Social Service officers, social companions, and the shelter coordinator. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model and verified through source triangulation. The results show that adult homeless individuals generally experience learned helplessness as a result of habitual begging for instant survival, accompanied by defensive attitudes and psychological trauma at the early stage of guidance. The application of humanistic counseling, through stages of field approach, assessment, trust-building, and problem-solving, incorporating Rogers's three core conditions of empathy, unconditional positive regard, and congruence, proved effective in fostering counselees' self-awareness after two to three guidance sessions. This impact was evident in increased confidence in their capacity to work and willingness to undertake recommended informal jobs suited to their individual capacities, although long-term success still depends on the emergence of independent responsibility from within the counselee, rather than mere compliance with the program.